Mobility of West Java Community After the Arrival of the Railway (1880-1930) - Syah, M Kautsar Thariq; Sa’adah, Putri Lailatus; Darmilah, Diah; Arsyad, Muhammad Fikri; Sugiarto, Deri; Nurcahya, Yan (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
The long journey of trains in Indonesia began during the Dutch colonial era in 1840 until today. Historically, the implementation of trains began during the Dutch East Indies Colonial Government. The reason is, the increasingly modern transportation infrastructure in the community that connects villages and cities, or cities with other cities is one of the drivers of community mobility. This study uses a historical method because it examines in depth the mobility of trains to the community. The scope of the study includes the history of the development of trains, historical manuscripts from archives. The construction of the railway line was very useful for plantation entrepreneurs to transport their garden produce. The Dutch East Indies government also saw the usefulness of the railway line for military purposes. The Priangan railway line during the Dutch colonial era was known as the Preangerlijn (Priangan Line). The line was built in the period 1880-1894. The Priangan Line has characteristics such as hilly and valley land contours, making the railway mode of transportation an efficient means of transportation for transporting passengers and agricultural products. The results of this study illustrate that the train has become a symbol of connectivity and progress so that people can feel the benefits of modern transportation that continues to develop to this day and has become an inseparable part of the journey of history and development in West Java.